Penerapan Profil Pelajar Pancasila dalam Pembentukan Karakter Peserta Didik - Dalman Dalman; Raehang Raehang; Laode Adhi Virama; Kharis Sulaiman (IAIN Kendari, 2022)
This study aims to assess the effects of putting the Pancasila student profile project into practice on the development of student character. This study is a review of the literature. As part of the literature search step, data gathering was done utilizing a database search tool. The Preferred Reporting Items for Systematic Review AND Meta-Analysis (PRISMA) approach is used for data collecting. According to the screening findings, there were four foreign and 11 national journals. Examining the article's findings demonstrates that the profile of Pancasila students promotes the development of decent people with six primary qualities, including faith, the awe of God Almighty, moral character, respect for world variety, reciprocal collaboration, independence, critical thinking, and creativity. For kids to be able to autonomously establish character values and noble character that can be realized in their lives, character values are taught to them as part of the learning process in the contexts of school, family, and community. Honesty, civility, discipline, responsibility, and religion are strengthened character qualities.Keywords: Pancasila student profile, student character, character building